التطور التاريخي للظاهرة الحزبية في لبنان أهم ملامحها وأنماطها (مجلة جامعة اللاذقية- سلسلة العلوم الاقتصادية والقانونية, 2016)
إنَّ من سمات لبنان التاريخية، الحرية السياسة والحيوية الزائدة، وهذا المدى المتنوع من القوى والأحزاب والتنظيمات التي تتراوح من أقصى اليمين إلى أقصى اليسار، وقد سمح بذلك التنوع فرادة الوضع السياسي في لبنان إزاء محيطه العربي، من حيث الخصوصية الناتجة عن البرلمانية والتنوع الطائفي ووجود الأقليات، وتنامي الميول الوسطية لدى القوى السياسية التي تشرعنت في الأحزاب خلال مراحل تاريخية محددة، فلكل كيان طائفي حزبه أو أحزابه، وهو متحصن بطائفته في وجه الحزب الأخر، وحتى في وجه الدولة أحياناً، فالطائفة تحد الطائفة والحزب مقابل الحزب. تتناول هذه الدّراسة، وبشكلٍ مكثفٍ التّطور التَّاريخي للظَّاهرة الحزبيَّة في لبنان، ومراحل نشأتها خلال الحقب الأساسيَّة التي مرّ بها الكيان اللٌّبناني منذ العهد العثماني، إلى عهد الاحتلال الفرنسي، فمرحلة الاستقلال الوطني–ما قبل الحرب الأهلية وخلالها وما بعدها- ثم تعرّجُ على الأنماط الأساسيَّة لهذه الأحزاب، لتنتقل إلى تناول أهم ملامح التَّجربة الحزبيَّة السّياسيَّة في لبنان. وتخلص إلى أنّ للنظام السّياسي تأثيرٌ كبيرٌ على الأحزاب، فكلُ نظامٍ ينتجُ أحزاباً على شاكلته. والنّظام اللّبناني باعتباره نظام الأفراد والعائلات والطّوائف، ونظام الإقطاع التّقليدي والمالي، أنتج نظاماً حزبياً على شاكلته، وثيق الارتباط بالنسيج الطّائفي المتشظّي لهذا المجتمع، سواء لجهة قوانين الانتخاب المتتاليَّة، أو قانون الجمعيَّات والأحزاب، أو قانون اللَّامركزية الإدارَّية، وكلها لا تساهم في توسيع مساحة العمل الحزبي، بل على العكس تساهم بإنتاج وإعادة إنتاج القوى التَّقليديَّة على حساب مؤسسات الدَّولة الحّديثة ومنها الأحزاب.فالتفتيت السياسي يعجز عن احتكار المميزات ويحمل بذور الاختلاف إلى حده الأقصى، فيحول الأحزاب عن مهمة الناظم لنزاعات المجتمع وضبط إيقاعها ويدفعها نحو الغلو في التمايز، ويأســر الحياة السياسية في حلبة عدم الاستقرار والتناحر.Lebanon is characterized through history by political freedom and over vitality , and diversity of forces , parties and organizations which alters from extreme right into extreme left . All that made political status in Lebanon a unique one compared to other status in the Arab surrounding , from the view point of exclusivity coming out of parliamentary circumstances , sectarian diversity , increasing approaches towards moderation of political forces which were legalized in the form of parties throughout specific historical stages .Each sectarian entity has its party or parties , which is fortified by its sect facing the other party and the state sometimes . Sect limits the sect and party against a party .This research approaches , profoundly , the historical development of the parties phenomenon in Lebanon and stages of its emergence during the basic periods through which Lebanon have passed since the Ottoman epoch till the period of French occupation and then the period are discussed , in addition to the most important features of the partisan experience in Lebanon . The research came to that political regime has its great effect on parties , as each political regime originates parties which comply with its form . Political regime in Lebanon as it is considered a regime of individuals , families and sects , and the traditional feudal and financial system , it originated a parties system which is similar to it , very close to the sectarian texture of the Lebanon society , from the view point of consecutive election laws , or the law of societies and parties , and the law of administrative decentralization , and all do not contribute to the expansion of the parties work area , but on the contrary this leads to the generation and regeneration of traditional forces to the disadvantage of modern state institutions and parties are of them . Political fragmentation is unable to monopolize privileges and it bears seeds of imparity to its maximum limit, so that it transforms the mission of parties from organizing and controlling society's disputes and it pushes towards extreme imparity , and it confines political life in the sphere of instability and conflict.